Barriers and facilitators to implementing advanced HIV disease screening at a secondary referral hospital -Malawi: a convergent parallel study - Brany Mithi; Agatha Bula; Lester Kapanda; Fatsani Ngwalangwa; Evanson Z. Sambala (BMC, 2023)
Abstract Background Malawi continues to register HIV/AIDS mortality despite increased expansion of ART services and as well as advanced HIV screening as outlined in the 2020 -2025 Malawi National HIV Strategic Plan (NSP). This study aimed to explore factors influencing the implementation of the advanced HIV disease (AHD) screening package at Rumphi District Hospital, Malawi. Methods We conducted a mixed method, convergent study at a secondary referral hospital with 8 659 clients on ART. Guided by a consolidated framework for implementation research (CFIR) we conducted semi-structured Interviews with healthcare professionals, purposively selected from various key departments that were actively involved in AHD screening. Transcripts were organized and coded using NVivo 12 software with thematically predefined CFIR constructs. Newly HIV-positive client records extracted from ART cards (July -Dec, 2021) were analyzed using STATA 14 software. Results One hundred one ART records met inclusion criteria for review and analysis of which 60% (n = 61) of the newly diagnosed HIV clients had no documented results for CD4 Cell count. Barriers to AHD screening emerged from four major CFIR constructs: intervention complexity, communication, availability of resources and access to knowledge and information. The specific barriers included poor work coordination among implementers, limited resources to support the expansion of AHD screening, and knowledge gap among providers. External support from Ministry of Health implementing partners and the availability of committed focal leaders coordinating HIV programs emerged as major enablers of AHD screening package. Conclusion The study has identified major contextual barriers to AHD screening including knowledge gap, poor communication systems and inadequate supporting resources. Improving uptake of AHD screening services would therefore require overcoming the existing barriers by adopting a comprehensive approach in developing barrier-tailored strategies.